The Ukrainian subject, hierarchies of knowledge production and the everyday: An autoethnographic narrative - Kurylo, Bohdana (Journal of international relations and development, 2023)
Russia’s full-scale war against Ukraine has exposed the dire lack of Ukrainian perspectives and the harmful presence of decontextualised analyses of the war in IR and related disciplines. This contribution contemplates the ways in which we could make the study of the war more attuned to the knowledges and agency of ordinary Ukrainians. It begins by identifying the epistemological, ontological and methodological hierarchies in academic knowledge production that result in effacing Ukrainian voices. These hierarchies manifest themselves in the Westplaining-ridden, elite-centric and depersonalised narratives of the war that circumscribe what counts as legitimate knowledge. In contrast, I stress the need to redirect attention to the oft-overlooked realm of the everyday and the lived experiences of Ukrainians. In the second part of the paper, I offer an autoethnographic account of the everyday struggles I went through as a Ukrainian citizen and academic located in the Western context in the immediate pre- and post-February 2022 periods. The result contributes to the broader efforts to move the subjugated knowledges of Europe’s East from the margins to the academic centre.